APPLICATION OF FINGER GRIP RELAXATION TECHNIQUES TO REDUCE PAIN IN POSTOPERATIVE PATIENTS IN ALAMANDA 2 ROOM, SLEMAN GENERAL HOSPITAL (RSUD SLEMAN) - Rafa Zahra Fauziyyah; Sumarti Endah Purnamaningsih Maria Margaretha (POLITEKNIK KESEHATAN KARYA HUSDA YOGYAKARTA, 2026)
Background: Postoperative pain is a common problem that can affect patient comfort, healing, and psychological well-being. Effective pain management should not rely solely on pharmacological therapy but also incorporate non-pharmacological techniques such as finger hold relaxation, which has been proven to reduce pain intensity. Objective: This study aims to describe the application of the finger hold relaxation technique in reducing postoperative pain in patients at Alamanda 2 Ward, Sleman Regional General Hospital. Methods: A descriptive case study design was used involving one postoperative appendectomy patient who reported a pain score of 5 according to the Numeric Rating Scale (NRS). The intervention was performed for 15 minutes, twice daily, over three consecutive days. Pain was measured before and after each session. Results: The results showed a gradual reduction in pain from 5 (moderate pain) to 2 (mild pain), accompanied by stable vital signs throughout the intervention period. Conclusion: The finger hold relaxation technique is effective, simple, and safe in reducing postoperative pain and can be considered a holistic, non-pharmacological approach to support patient recovery.